PERBEDAAN QIRA’AT DALAM AN-NAQSH WA AZ-ZIYĀDAH DAN PENGARUHNYA TERHADAP FLEKSIBILITAS HUKUM - Sitti Nur Sapiah Husnah; Abdur Rokhim Hasan; Fakhri 'Adani (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2026)
Differences in Qur’anic qira’at not only demonstrate the diversity of recitations, but also have implications for the interpretation of Qur’anic verses. One form of these differences is an-naqsh wa az-ziyādah, namely the omission (naqsh) and addition (ziyadah) of lexical elements in various qira’at narrations. Although this phenomenon has long been discussed in classical Islamic literature, studies specifically examining its exegetical implications remain relatively limited. Therefore, this study aims to identify the forms of an-naqsh wa az-ziyādah in qira’at and analyze their implications for Qur’anic interpretation. This research employs a qualitative method with a library research approach. Data were collected from classical qira’at works, literature on ‘ulūm al-Qur’an, tafsir books, and Indonesian academic journals. The analysis was conducted using a linguistic approach to identify forms of omission and addition in lexical structures, as well as comparative and exegetical approaches to examine differences in meaning arising from qira’at variations. The findings reveal that an-naqsh wa az-ziyādah in qira’at includes variations at the levels of letters, words, and sentence structures, all of which influence the nuances of Qur’anic meaning. These differences are not contradictory; rather, they complement one another and enrich the dimensions of interpretation. In several cases, such variations also affect differences in emphasis of meaning and the process of legal deduction (istinbāṭ al-aḥkām). This study confirms that qira’at play a strategic role in Qur’anic exegesis, making the understanding of an-naqsh wa az-ziyādah essential for achieving a more comprehensive, integrative, and contextual interpretation of the Qur’an.